(untitled) (Research, Society and Development, 2022)
The study aimed to assess compliance with clinical protocol and therapeutic guidelines (CPTG) for dyslipidemia for the prevention of cardiovascular events and pancreatitis. This was a retrospective observational study of medication release processes for the treatment of dyslipidemia in medication dispensing pharmacies of the specialized component of pharmaceutical service and analytical-descriptive guidance of a qualitative nature with pharmacists and system managers. The processes of patients undergoing treatment with statins and fibrates and with data from at least one year of medication use and also pharmacists working in the dispensing of medications and managers were included in the research. A total of 146 processes were analyzed and 36 pharmacists and 6 managers participated in the qualitative approach. Ninety cases (61.6%) presented the described inclusion criteria. Only in seven (19.4%) cases the initial triglyceride values were above 500mg/dL and in 72.3% the values were lower than recommended. No report of exclusion criteria was identified for users of the analyzed processes, however, in relation to hyperthyroidism, 2.1% processes had TSH levels above 10mcUI/mL and 7.5% had no data on the dosage of this hormone. Initial measurements of CPK and liver transaminases were not present in 10 (6.8%) and 5 (3.4%) cases, respectively. In conclusion, it was possible to understand that there is no effective compliance with what is standardized in the PCDT for dyslipidemia and that the continuing education of professionals and management commitment to this continuous improvement must be priorities to ensure the safety and effectiveness of the treatment.